Gus Dur's Philosophical Approach to Pluralism: Insights for Social Harmony in Indonesia - Safitri, Neng Nurya (Islamic Thought Review, 2024)
This study explores the seminal thoughts of Kyai Haji Abdurrahman Wahid, widely known as Gus Dur, a distinguished advocate of pluralism in Indonesia. Gus Dur regarded diversity as an inherent and invaluable aspect of human existence, deserving of respect and preservation. Indonesia, celebrated for its cultural and religious diversity, simultaneously faces significant challenges in sustaining societal harmony amidst its pluralistic landscape. The research aims to critically analyze Gus Dur's perspectives on human values, tolerance, and pluralism, offering them as a conceptual framework for fostering a harmonious and inclusive society in Indonesia. Employing a qualitative methodology with a literature review approach, this study draws upon primary sources including Gus Dur's writings, speeches, and related scholarly works. The findings reveal Gus Dur's strong emphasis on intercultural dialogue, the promotion of social justice, and the safeguarding of religious freedom as foundational elements of pluralism. Moreover, he advocated for educational reforms to cultivate values of tolerance, pluralism, and the internalization of Pancasila as the ideological bedrock of national unity. By synthesizing Gus Dur's pluralistic vision, this study makes a significant contribution to academic discourse, providing actionable insights into strategies for enhancing social cohesion, embracing diversity, and building an inclusive and harmonious society, particularly within the context of Indonesia’s multiculturalism.